Morphology, structure and kinematics of a rainfall controlled slow‐moving Andean landslide, Peru. Issue 11 (24th February 2016) - Zerathe, Swann; Lacroix, Pascal; Jongmans, Denis; Marino, Jersy; Taipe, Edu; Wathelet, Marc; Pari, Walter; Smoll, Lionel Fidel; Norabuena, Edmundo; Guillier, Bertrand; Tatard, Lucile
Abstract: The large slow‐moving landslide of Maca is located in the upper Colca valley (southern Peru), a region characterized by a well pronounced rainy period, and intense and recurrent sustained seismicity. The landslide, developed in deep lacustrine deposits, has recently accelerated, threatening the Maca village. This work aims at understanding the rupture mechanism and the causes of the recent landslide reactivation/acceleration. We present a multidisciplinary characterization of the Maca landslide that includes: (i) geological and morphological mapping in the field; (ii) remote sensing analysis using an historical aerial photograph of 1955 and the Pléiades satellite images (2013); (iii) global positioning system (GPS) including time‐series of surveys over 13 years, and continuous measurements over 14 months; (iv) a geophysical campaign with deep electrical resistivity tomography profiles acquired across the landslide mass. Our study shows that this 60 Mm 3 landslide, which can be classified as a clay/silt compound landslide, moved by 15 m between 2001 and 2014 with a large inter‐annual velocity variation (up to a factor of 500) depending on the rainfall intensity. We suggest that these dramatic changes in velocity are the result of the combination of a threshold mechanism and the short intense rainy season in Peru. This study reveals three main driving factors acting at different timescales: (i) over several decades, the river course has significantly changed, causing the Maca landslide reactivation in the 1980s due to the erosion of its toe; (ii) at the year scale, a minimum amount of rainfall is required to trigger the motion and this amount controls the landslide velocity; (iii) transient changes in slide velocity may occur anytime due to earthquakes. This study particularly highlights the non‐linear behaviour of the motion with rainfall. Copyright © 2016 John Wiley & Sons, Ltd.